Sektor Industri Pada Pemetakan Peluang Ekonomi Makro Kota Surabaya - Salsabilla Saifana Veriyanto; Muhammad Yasin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The industrial sector is a strategic sector in the development of the national economy to address the problem of unemployment. In economic opportunities, being able to provide opportunities related to the management of material, resources, individuals, society, and the state for the welfare of human life so that there are no drastic economic disparities. The purpose of this study is to find out how important the industrial sector is in economic opportunities in the city of Surabaya. The research method used is quantitative method is data measured on a numerical scale (number) for data collection by means of secondary analysis where the data is obtained from other parties and indirectly from the research subject. Usually secondary data in the form of documentation or report data that has been available.